2009
DOI: 10.1111/j.1365-2028.2008.01053.x
|View full text |Cite
|
Sign up to set email alerts
|

Scattered trees as modifiers of agricultural landscapes: the role of waddeessa (Cordia africana Lam.) trees in Bako area, Oromia, Ethiopia

Abstract: Scattered trees in general and scattered waddeessa (Cordia africana Lam.) trees in particular are very common across the agricultural landscapes in Oromia, Ethiopia. A study on this scattered waddeessa trees commonly growing on farmers’ agricultural fields was conducted at Bako in western Oromia, Ethiopia with the objective of assessing their role in modifying the soil properties in the agricultural landscape. Soil samples from surface layers (0–10 cm) were taken at three concentric transects (0.5, 2 and 4 m) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 14 publications
2
21
0
Order By: Relevance
“…This study agrees with substantial amount of available phosphorus found under the tree canopy by different scholars (Tadesse Hailu et al,2000) who observed higher available soil phosphorus status in the surface soils than in the subsurface and under the canopy of Millettia ferruginea trees than in the open field. Similar trends were also reported under Faidherbia albida and Cordia africana on farm lands in Ethiopia (Kamara and Haque, 1992;Abebe Yadessa et al, 2009). In contrast to the present investigation, (Enideg Diress, 2008) reported no change in available phosphorus status between soils under canopy of Ficus thonningiiand open area in Gonder zuria, Ethiopia.…”
Section: Soil Ph Electrical Conductivity Organic Carbon Total Nitrsupporting
confidence: 81%
“…This study agrees with substantial amount of available phosphorus found under the tree canopy by different scholars (Tadesse Hailu et al,2000) who observed higher available soil phosphorus status in the surface soils than in the subsurface and under the canopy of Millettia ferruginea trees than in the open field. Similar trends were also reported under Faidherbia albida and Cordia africana on farm lands in Ethiopia (Kamara and Haque, 1992;Abebe Yadessa et al, 2009). In contrast to the present investigation, (Enideg Diress, 2008) reported no change in available phosphorus status between soils under canopy of Ficus thonningiiand open area in Gonder zuria, Ethiopia.…”
Section: Soil Ph Electrical Conductivity Organic Carbon Total Nitrsupporting
confidence: 81%
“…growing trees and shrubs by farmers on available land in any pattern for the purpose of providing forest products (construction wood, animal feed, fuelwood, small construction materials) (Shastri et al 2002;Holden et al 2003;Kidanu et al 2004;Rahman et al 2005) and services (e.g. soil amelioration (Gindaba et al 2005;Manning et al 2006;Yadessa et al 2009), soil erosion control, shade for domestic animals, property demarcation, microclimate amelioration for the farm households) receives increasing attention among farmers these days. For them, it is a means of coping with the scarcity of forest products caused by the depletion of forests.…”
Section: Introductionmentioning
confidence: 99%
“…Soil samples (0-20 cm) were collected from each plot. Five samples were collected per plot and then bulked to obtain a composite sample, and finally one representative sample was taken from the bulk per plot as described in Yadessa et al (2001Yadessa et al ( , 2009. Soil samples were analyzed for chemical and physical properties following the standard procedures.…”
Section: Soil Sampling and Analysismentioning
confidence: 99%